The study of the climate in the past and the climate change in mainland portugal using geothermal data has started in 199 - Correia, António (Finisterra, 2012)
The study of the climate in the past and the climate change in mainland portugal using geothermal data has started in 199. Reconstruction of ground surface temperature (GST) history from temperature logs measured in a 200 m deep borehole located 5 km away from the town of évora in portugal, indicates a warming of 1K since the second half of the nineteenth century to the middle of the 90s of the twentieth century, increasing considerably in the last 10 years. Results of the reconstruction (based on a functional space inversion – FSI – method) are compared with air temperatures recorded at the lisbon meteorological station since 185. The air temperature time series display a warming trend with the amplitude about 1K for the same period. The coupling of the air and ground temperature changes and their downward propagation by heat conduction was confirmed by repeated logging in November 2003, .7 years after obtaining the first temperature log. The method can be used in paleoclimatic studies in Antarctica as well as in areas with permafrost. : Finisterra, vol. 44 n.º 87 (2009)